A parametric study on the efficiency of a solar evacuated tube collector using phase change materials: A transient simulation. (November 2022) - Feng, Li; Liu, Jiajun; Lu, Haitao; Chen, Yuning; Wu, Shenyu
Abstract: Evacuated solar collectors are renewable systems that provide a considerable quantity of heat during test time. However, this system is unable to provide energy in the absence of sunlight. Thus, this study attempted to numerically study a Solar Evacuated Tube Collector (ETC) performance using phase change materials (PCM). PCM can store considerable thermal energy during the day and release it to the system at night. In order to simulate the ETC-PCM system, an accurate three-dimensional model considering all the layers is designed. In the present numerical investigation, the effect of various properties of the PCM, including enthalpy, melting point, and thermal conductivity, on the outputs of the ETC-PCM system are evaluated separately. Also, the effects of some other factors, such as MWCNT nanoparticles dispersion in the base fluid and working fluid mass flow rate, on the performance of the ETC-PCM system are studied. Furthermore, to evaluate the performance of the system and model the behavior of the PCM during the day, the system is simulated under the weather condition of Hing Kong from sunrise until sunset. According to the results of the simulations, a reduction in PCM melting point from 50 °C to 35 °C can elevate the efficiency of the ETC-PCM device. PCM with a high melting point remains solid during the day. Thus, its effect on the output of the system cannot be revealed. Moreover, it is found that the system using PCM with the latent heat of 160 kJ/kg has the best performance among the studied cases. Besides, it is illustrated that raising the mass flow rate of working fluid and mass fraction of nanoparticles can enhance the system's performance. Graphical abstract: Image 1